Toward a Narrative-Critical Understanding of Luke - Tannehill, Robert C. (Interpretation, 1994)
Tabitha and Cornelius, imaginary persons based on characters in Acts, occupy two different places in the first-century Mediterranean world. In hearing Luke's gospel-story, how would each construe the figure of Jesus? The social location of each would play a crucial role as each "builds" the character of Jesus in dialogue with Luke's story